Ensuring the quality of basic service delivery in decentralised local governments through the Minimum Service Standard policy: How does it work? - Purwanto, Erwan Agus; Pramusinto, Agus; Margono, Subando Agus (2019)
This paper discusses the impact of the implementation of Minimum Service Standard (MSS) policy on the quality of basic services district/city governments deliver to their citizenry in Indonesia. One of the expectations of the decentralisation policy, which got underway in 1999 was to contribute to the improvement of the quality of public services. The issuing of Indonesian Government Regulation (GR) No. 65/2005, which outlined guidelines on setting and implementing MSS for all sectoral ministries was very much in line with that process. Study results obtained from a survey of the local government officials attest to the reality that most local governments are yet to implement the 15 MSS set by the 15 sectoral ministries. Some of the factors that have hampered the implementation of MSS include lack of clarity on substance of MSS policy (unclear concept of basic services and MSS; variety of approaches used in various sectoral ministries, such as input, process, output and outcome), and constraints that implementing organisations face (insufficient budget allocation and human resource capacity, unclear functional assignments, and lack of integration of MSS in local government development plans). Copyright © 2019 Inderscience Enterprises Ltd.